Wozu Algebra der Logik? Ernst Schröders Suche nach einer universalen Theorie der Verknüpfungen - Peckhaus, Volker (Modern Logic)
Abstract: Historia Mathematica 22 (1995), #22.2.62 (I. Anellis). Rezensionen: Zbl. Math. 812.01012 (I. Grattan-Guinness); MR 95m:03002 (M. Guillaume).

Die Gleichstellung der Geschlechter im Lehrplan. Anregungen für Schule und Unterricht. - Bigga, Regine; Braun, F.; Hoffmann, L.

Erwerbsarbeit - Hausarbeit. Strukturwandel der Arbeit als Herausforderung an das Lernfeld Arbeitslehre - Tornieporth, G.; Bigga, Regine

Ergebnisse aus dem Projekt Mädchen & junge Frauen in der Arbeitswelt - Bigga, Regine (Erwerbsarbeit - Hausarbeit. Strukturwandel der Arbeit als Herausforderung an das Lernfeld der Arbeitslehre)

The Development of Ernst Schröder’s Attitude towards Logic [Abstract] - Peckhaus, Volker (XIXth International Congress of History of Science. 22–29 August 1993 Zaragoza (Spain). Book of Abstracts Symposia)

Leibniz’ ,Mathesis universalis‘ und die Mathematiker des 19. Jahrhunderts [Abstract] - Peckhaus, Volker (Fachsektion Geschichte der Mathematik der Deutschen Mathematiker-Vereinigung. Sektionstagung vom 22. bis 26. März 1993 in Wuppertal)

Hinweise zur Modellbildung und Simulation des Strahlungseinfalls in PV-Module - Krauter, Stefan (Solar Energy Simulation Workshop der DGS, Oldenburg (Deutschland))

Efficient PRAM simulation on a distributed memory machine - Karp, Richard M.; Luby, Michael; Meyer auf der Heide, Friedhelm (Proceedings of the twenty-fourth annual ACM symposium on Theory of computing - STOC '92)

Trellis codes for partial-response magnetooptical direct overwrite recording - Haeb-Umbach, Reinhold; Lynch, Robert (IEEE Journal on Selected Areas in Communications)
The authors present conditions on the error sequences between channel input sequences which guarantee certain lower bounds on the free Euclidian distance at the output of a partial-response (PR) class I or II channel. From these expressions, trellis codes are derived which improve performance of binary signaling over noisy PR channels with reduced complexity maximum-likelihood sequence detection. They are shown to be compatible with the input restriction caused by the magnetooptical resonant coil direct overwrite recording scheme. The codes achieve high signal-to-noise ratio coding gains of 3 dB (on PR class I) and 2.2 dB (on PR class II) with rates as close to, but strictly less than, the capacity of the initial input restriction as desired. The performance of these codes is analyzed with an optical channel simulation system which shows that one code has the rare but highly desirable property that its maximum-likelihood sequence detector (MLSD) is less complex than the MLSD of the reference system and still achieves an error rate performance gain of 1.8 dB

Forschungsergebnisse zur Geschlechterfrage - Konsequenzen für die Gestaltung von Unterricht sowie für die Aus- und Weiterbildung von Lehrkräften - Bigga, Regine (Lehrplanrevision in Schleswig-Holstein)